탄성파 자료의 가스 지시자 분포 도출을 위한 기계 학습 활용 - 원종필; 전형구; Jongpil Won; Hyunggu Jun (자원환경지질, 2024)
The bright spot and seismic chimney, which are prominent gas indicators observed in seismic data, exhibit distinct geophysical features such as high amplitude, phase reversal, low continuity, and frequency attenuation. As a result, seismic attribute analysis has been widely applied to derive gas distributions within subsurface media. However, seismic attribute analysis has limitation that it is difficult to clearly distinguish gas indicators from other strata with similar geophysical properties. Therefore, this study proposes a machine-learning method to predict the distribution of bright spot and seismic chimney within seismic data. To effectively predict gas indicators in complex seismic data, the study constructed training data by simultaneously using noise-reduced seismic data and various seismic attribute analysis results. The proposed method was applied to 3D seismic survey data acquired from the F3-block in the North Sea, Netherlands to verify the effectiveness of the proposed method. The gas indicator distribution predicted by the trained model demonstrated higher accuracy and consistency compared to traditional multi-seismic attribute analysis results. Additionally, sensitivity analysis and a forward selection method were applied to optimize the selection of input data, confirming that the prediction accuracy was improved when input with low sensitivity was removed. 탄성파 자료상에 나타나는 대표적인 가스 지시자인 명점과 탄성파 침니는 각각 강한 진폭, 위상 역전, 낮은 연속성, 주파수 감쇠와 같은 지구물리학적 특성을 가지므로 지층 가스 분포 도출을 위해 탄성파 속성 분석이 널리 적용되어 왔다. 하지만 탄성파 속성 분석은 유사한 물리적 특성을 가지는 다른 지층들과 가스 지시자를 명확하게 구분하기 어렵다는 한계를 가지고 있다 . 따라서 본 연구는 탄성파 탐사 자료를 활용하여 지층 내 가스 지시자인 명점과 탄성파 침니의 분포를 예측하기 위한 기계학습 적용을 제안한다. 복잡한 탄성파 자료에서 가스 지시자를 효과적으로 예측하기 위해서 잡음이 제거된 탄성파 자료와 다양한 탄성파 속성 분석 결과를 동시에 활용하여 학습 자료를 구축하였다. 제안된 방법을 네덜란드 북해 F3-block에서 취득된 3차원 탄성파 탐사 자료에 적용하여 가스 지시자 분포 예측의 유효성을 검증하고자 하였다. 학습된 모델을 통해 예측된 가스 지시자의 분포는 기존 다중 탄성파 속성 분석 결과에 비해 높은 정확도와 일관성을 보였다. 또한 최적의 입력 자료 선정을 위해 민감도 분석 및 전진 선택 방식을 적용하였으며, 민감도가 낮은 입력 자료를 제거한 경우 예측의 정확도가 더 향상됨을 확인하였다.